Automatic 3D liver segmentation based on deep learning and globally optimized surface evolution. (23rd November 2016) - Hu, Peijun; Wu, Fa; Peng, Jialin; Liang, Ping; Kong, Dexing
Abstract: The detection and delineation of the liver from abdominal 3D computed tomography (CT) images are fundamental tasks in computer-assisted liver surgery planning. However, automatic and accurate segmentation, especially liver detection, remains challenging due to complex backgrounds, ambiguous boundaries, heterogeneous appearances and highly varied shapes of the liver. To address these difficulties, we propose an automatic segmentation framework based on 3D convolutional neural network (CNN) and globally optimized surface evolution. First, a deep 3D CNN is trained to learn a subject-specific probability map of the liver, which gives the initial surface and acts as a shape prior in the following segmentation step. Then, both global and local appearance information from the prior segmentation are adaptively incorporated into a segmentation model, which is globally optimized in a surface evolution way. The proposed method has been validated on 42 CT images from the public Sliver07 database and local hospitals. On the Sliver07 online testing set, the proposed method can achieve an overall score of 80.3 ± 4.5, yielding a mean Dice similarity coefficient of 97.25 ± 0.65 %, and an average symmetric surface distance of 0.84 ± 0.25 mm. The quantitative validations and comparisons show that the proposed method is accurate and effective for clinical application.